Economic viability of electric roads compared to oil and batteries for all forms of road transport. (December 2017) - Connolly, D.
Abstract: The aim in this paper is to evaluate the economic viability of electric vehicles that are supplemented by electric roads (eRoads), instead of using conventional diesel, petrol, and battery electric vehicles (BEVs). The battery is the most expensive component of an electric vehicle, so the premise of this paper is to reduce the size of the battery, and thereby significantly reduce the cost, by installing a series of electric roads for long-distance journeys. Denmark is used here as case study to ensure the assumptions reflect a real-world case when comparing petrol, diesel, BEVs, and eRoads. The results suggest that eRoads are a cheaper method of electrifying road transport than BEVs, which is an important finding, since electrification is widely believed to be the cheapest method for decarbonising the transport sector in the coming decades. Furthermore, if fuel and vehicle prices evolve as predicted between now and 2050, then eRoads are also a cheaper form of road transport than diesel and petrol, primarily due to increasing oil prices and decreasing battery costs. By implementing eRoads, it is also possible to electrify heavy-duty transport such as buses and trucks, which results in even more energy savings and reductions in carbon dioxide emissions. Highlights: Electric roads are compared to diesel, petrol, and battery electric vehicles. Electric roads are cheaper than battery electric vehicles in all scenarios. Oil is cheaper than electric roads today, but more expensive in the future. Energy consumption and carbon emissions are lowest with electric roads. Electric roads can electric heavy-duty transport such as trucks and buses.